Generation of osteoclast-like cells from human peripheral blood mononuclear cells using NFATc1 modified RNA - Sirada Srihirun; Chareerut Phruksaniyom; Thanaporn Sriwantana; Tipparat Parakaw; Nathawut Sibmooh; Pornpun Vivithanaporn; Kran Suknuntha (PLoS ONE, 2026)
Inhibition of osteoclasts, a type of bone-resorptive cell, is a key approach for treating diseases associated with bone loss. Although human osteoclasts can be generated from receptor activator of nuclear factor-ĸB ligand-mediated stimulation of peripheral blood mononuclear cells (PBMCs) in vitro, the differentiation rate is low and the process is time consuming. Here, we aimed to generate osteoclast-like cells from human PBMCs using modified RNA (modRNA) enforcing NFATc1 , a master transcription factor that functions downstream of receptor activator of nuclear factor-ĸB receptor activation. Human PBMCs isolated from the venous blood of healthy donors (n = 3) using Histopaque density gradient centrifugation were expanded in medium supplemented with 25 ng/mL macrophage colony-stimulating factor for 3 days. The isolated macrophages were transfected with NFATc1 modRNA. The osteoclast-like cells were evaluated for the following osteoclast-specific markers: tartrate-resistant acid phosphatase-positive expression, F-actin ring formation, cathepsin expression, and bone resorption activity. Scanning electron microscopy was used to morphologically characterize the osteoclast-like cells. At day 1 posttransfection with 25, 50, and 100 ng/mL of modRNA, NFATc1 expression in human macrophages increased by 1.20 ± 0.08-fold, 3.47 ± 1.02-fold, and 13.31 ± 3.96-fold, respectively. Transfection with 25 or 50 ng/mL of NFATc1 modRNA for 3 days induced the formation of tartrate-resistant acid phosphatase-positive multinucleated cells, the F-actin ring formation, expression of cathepsin K, and increased bone resorption activity. Scanning electron micrographs confirmed the presence of round, multinucleated cells with projecting microvilli, characteristic of osteoclasts. In conclusion, rapid generation of functional osteoclast-like cells was achieved in vitro using NFATc1 modRNA. This method offers faster results compared with conventional receptor activator of nuclear factor-ĸB ligand stimulation.